THE HELLENISTIC BIG ROCK HUMAN HEAD FROM BULGARIA - Metodi Yordanov Manov (Journal of Ancient History and Archaeology, 2018)
The subject of this paper is the impressive in its size rock image of a human head from the rock sanctuary located in the area Gradishteto, near the modern village of Dolno Dryanovo, Blagoevgrad region, Bulgaria. The place in that area is defined as a prehistoric and Thracian rock sanctuary and one of the oldest megalithic sanctuaries in Southeastern Europe. The attention here is focused only to the big rock head from the sanctuary of Dolno Dryanovo and an attempt is made to identify this remarkable image as well as its dating, and also to answer the question – who exactly has ordered making it to this place. According to the detailed observations of the magnificent rock portrait image and having used the most suitable parallels, including gold and silver coins, as well as two marble portrait images and one made of a black basalt, kept respectively in three major world museums, the conclusion was formed, that the big rock human head from Bulgaria in fact is a magnificent portrait image of Ptolemy I Lagos, king of Hellenistic Egypt. According to the author of the paper here, this quite large in size and majestic rock portrait of the king of Hellenistic Egypt, Ptolemy I, was made in the lands of ancient Thrace by order of the king of the Celtic/Galatian kingdom in Thrace, Kavaros. Because it was already found that the king Kavaros was the grandson of Ptolemy I on the side of his mother. It was made around the middle of the 3rd c. BC as an apotheosis of the king of Egypt. Only in this historical context can be explained making this grandiose rock portrait image of Ptolemy I in the lands of ancient Thrace – now in present-day Bulgaria. In fact, this is the greatest portrait image of the deified king Ptolemy I Soter, ever seen in the world.